Kebiasaan Sarapan pada Anak di SDN 09 Kenagarian Sijunjung - Eka Desnita; Yahdian Rasyadi; Nopan Saputra; Novia Asti Rahayu; Fadila Reza Putri; Alvi Yusra (FORUM ILMIAH KESEHATAN, 2023)
The breakfast pattern contributes to meeting the energy and nutritional needs of children. Not all children of school age have breakfast. This study aims to analyze breakfast habits in elementary school-age children. This research involved 80 students of SDN 09 Kenagarian, Sijunjung. In this descriptive study, children's knowledge of the importance of breakfast was measured by filling out a questionnaire. From the results of data analysis, 86.25% of students had breakfast every day, 82.5% had breakfast at home, 85% of parents played a role in reminding the importance of breakfast, 78.75% of parents accompanied their children at breakfast, 72.5% of students understood that breakfast important to do every day, and 61.25% of students understand the importance of the nutritional value that is fulfilled in breakfast. From the results of this study it could be concluded that most of the students actively had breakfast, but there were still many who did not understand that fulfilling the required nutritional value was important in breakfast. Most parents play an active role in supporting the fulfillment of student breakfast.Keywords: breakfast; elementary school students; habitABSTRAK Pola sarapan berkontribusi terhadap pemenuhan kebutuhan energi dan gizi pada anak. Tidak semua anak di usia sekolah bersarapan. Penelitian ini bertujuan untuk menganalisis kebiasaan sarapan pada anak usia sekolah pendidikan dasar. Penelitian ini melibatkan 80 siswa SDN 09 Kenagarian, Sijunjung. Dalam penelitian deskriptif ini, pengetahuan anak tentang pentingnya sarapan diukur melalui pengisian kuisioner. Dari hasil analisis data, 86,25% siswa sarapan setiap hari, 82,5% sarapan di rumah, 85% orang tua berperan mengingatkan pentingnya sarapan, 78,75% orang tua menemani anak ketika sarapan, 72,5% siswa memahami bahwa sarapan penting dilakukan setiap hari, dan 61,25% siswa memahami tentang pentingnya nilai gizi yang terpenuhi dalam sarapan. Dari hasil penelitian ini dapat disimpulkan bahwa sebagian besar dari siswa aktif sarapan, namun masih banyak yang belum memahami bahwa terpenuhinya nilai gizi yang dibutuhkan adalah penting dalam sarapan. Sebagian besar orang tua berperan aktif mendukung terpenuhinya sarapan siswa.Kata kunci: sarapan; siswa sekolah dasar; kebiasaan